Toward sustainable and economic smart mobility shaping the future of smart cities - Eiza, Max; Cao, Yue; Xu, Lexi (World Scientific, 2020)
During the last decade, developments in smart cars, mobile devices, Internet of Things and vehicular communications have transformed the future of smart cities. With the rapid integration of these smart devices into our surroundings, as we enter into a new era of a highly connected and environmentally friendly ecosystem. This book offers a unique opportunity for the reader to explore state-of-the-art developments in applications, technologies (such as Big Data and Artificial Intelligence), services and research trends in smart mobility for smart cities. It also provides a reference for professionals and researchers in the areas of Smart Mobility (e.g. autonomous valet parking, passenger trajectory data, smart traffic control systems) and recent technical trends on their enabling technologies. The materials have been carefully selected to reflect the latest developments in the field with many novel contributions from academics and industry experts from around the world.
Keywords: Intelligent transportation systems; Transportation / Technological innovations; Transportation / Management; Communication and traffic; Sustainable development; City planning / Technological innovations; Mobilität; Smart City; Nachhaltigkeit; Aufsatzsammlung